PERAN VISI, MISI, DAN TUJUAN DALAM MEMBANGUN KARAKTER ANAK USIA DINI DI TK TUNAS BANGSA - Finnas, Fara Fauza; Hamam Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of vision, mission, and goals in building the character of early childhood at Tunas Bangsa Kindergarten. The study used a qualitative approach with a field study type. The research subjects included the principal, teachers, and students who were selected purposively. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis used an interactive model through data reduction, data presentation, and drawing conclusions, and its validity was tested by triangulation of sources and techniques. The results of the study indicate that the vision, mission, and goals have a strategic role as the main foundation in shaping the character of early childhood. The vision serves as the direction and identity of the institution, the mission as a form of implementation through learning activities and habits, and goals as indicators of success in assessing children's character development. Implementation is carried out in an integrated manner through habituation activities such as prayer, congregational Dhuha prayer, maintaining cleanliness, and learning that instills the values ​​of discipline, responsibility, independence, and empathy. Thus, this study confirms that the success of character education in early childhood is largely determined by the alignment between the vision, mission, and goals with holistic, sustainable, and contextual learning practices. Keywords: vision, mission, goals, early childhood